Monte Carlo Method for Evaluation of Uncertainty in Topometry by Using In-Plane Electronic Speckle Pattern Interferometry with Divergent Illumination - Cordero-Carrasco, R (2011)
Electronic speckle pattern interferometry is a useful technique in the measurement of displacement fields and topography. Traditionally, arrangement with dual collimated illumination to topography measurement is used. In this case, the object analysis is limited to the size of optical collimating lens. In the case of large objects, an optical system with divergent illumination can be used. It is known that displacement fields and the phase are related by the sensitivity vector. At once, to compute the sensitivity vector, illumination sources position and superficial shape need to be considered. The last condition becomes an impediment to surface contouring. In a published work1, a simple iterative algorithm based on the Gauss-Seidel technique is presented to compute contouring measurement. In the present work, the uncertainty associated to the measurement of the topography is calculated by using the Monte Carlo method. © 2011 SPIE.